Pengaruh Media Video Animasi terhadap Kemampuan Membaca Permulaan - Firbi Utami; Kowiyah Kowiyah (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2022)
This research aims to study was to see whether there was an effect of animated video media on the early reading ability of the 1st graders of SD Negeri 13 Toboali. The approach used is quantitative in the form of an experiment or can be called, pre-experimental. The research design used in this research is the one-group pretest – posttest. The population in this study were all students of class I/B SDN 13 Toboali, totaling 26 students. The sampling technique in this study was a saturated sample. The instrument used in this study was in the form of questions to measure initial reading ability. The results of this study with the pretest value which was initially 51.923 to 77.692 after the posttest. This result is also seen from the results of hypothesis testing, namely, count > table with a value of 10,775 > 1,782, so the conclusion is H0 is accepted, meaning that there is an Effect of Animated Video Media on Beginning Reading Ability of First Grade Students of SD Negeri 13 Toboali.